Nonionic surfactant vesicles for delivery of RNAi therapeutics - Paecharoenchai, Orapan (2013)
RNAi is a promising potential therapeutic approach for many diseases. A major barrier to its clinical translation is the lack of efficient delivery systems for siRNA. Among nonviral vectors, nonionic surfactant vesicles (niosomes) have shown a great deal of promise in terms of their efficacy and toxicity profiles. Nonionic surfactants have been shown to be a superior alternative to phospholipids in several studies. There is a large selection of surfactants with various properties that have been incorporated into niosomes. Therefore, there is great potential for innovation in terms of nisome composition. This article summarizes recent advancements in niosome technology for the delivery of siRNA.